2002
DOI: 10.1023/a:1020846007149
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Implantable cardioverter defibrillators (ICDs) are now an accepted and effective therapy for treatment of survivors of sudden cardiac death (SCD) and prevention of SCD in high-risk patients. Normal ICD function and delivery of therapy depends on appropriate sensing and detection of myocardial electrical potentials. Electromagnetic interference resulting in ICD malfunction is a well-documented phenomenon, however, there are less well-known external sources of interference, which may cause life threatening ICD m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…This potential issue is also applicable to S-ICDs. 3,11,12 Despite manufacturers implementing specific measures and precautions to address EMI in CIEDs, numerous case studies have reported instances where CIEDs administer inappropriate shocks due to EMI interference. Consequently, there are challenges and complexi-ties in mitigating the impact of EMI on the proper functioning of these devices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This potential issue is also applicable to S-ICDs. 3,11,12 Despite manufacturers implementing specific measures and precautions to address EMI in CIEDs, numerous case studies have reported instances where CIEDs administer inappropriate shocks due to EMI interference. Consequently, there are challenges and complexi-ties in mitigating the impact of EMI on the proper functioning of these devices.…”
Section: Discussionmentioning
confidence: 99%
“…in the literature, underscoring the importance of comprehensively examining these occurrences for proper identification and proactive prevention. 3,11,12 An electromagnetic field may generate currents in the lead, resulting in local fibrillation or heating in the heart or induce voltage in the lead. Damage to the CIED and interference with the device's ability to accurately monitor the intrinsic heart signal may occur.…”
Section: Numerous Instances Of Icd Malfunctions Have Been Documentedmentioning
confidence: 99%
“…EMI resulting in ICD malfunction is a well-known phenomenon 4. Source of EMI may be a normally functioning device including electronic article surveillance systems, hand-held radiofrequency remote controls, slot machines, abdominal muscle stimulators, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Possuem, entretanto, fatores de risco inerentes, podendo estar relacionados a vários tipos de erros (Garg et al, 2002;Kaczmarek et al, 2000), inclusive devido à calibração inexistente ou inadequada (Fitzgibbon et al, 2004).…”
Section: Introductionunclassified